KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KECERDASAN LOGIS MATEMATIS KELAS VIII - Umiati, Umiati; Hamdani, Hamdani; BS, Dian Ahmad (Jurnal AlphaEuclidEdu, 2023)
This research aims to determine mathematical communication skills of students in terms of mathematical logical intelligence. The research method used is descriptive quantitative. The subjects of this study were 29 students of class VIII SMP Negeri 3 Pontianak. Data collection techniques used are direct measurement techniques and communication. Data collection tools used are test questions and interview guidelines. The results of the research generally show that mathematical logical intelligence is obtained by 74% in the high category, while the mathematical communication ability is obtained by 54% in the low category. Students who have high mathematical logical intelligence tend to have high mathematical communication skills, while students with low mathematical logical intelligence tend to have low mathematical communication skills